Validating Curriculum-Based Measurement Oral Reading Fluency (CBM ORF) Applicability To Evaluate Arabic Readers’ Performance - Alqahtani, Saeed Saad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
While curriculum-based measurement (CBM) accurately indicates reading skills, such as progress monitoring and early detection of reading difficulty, it has yet to be developed for Arabic. This study aimed to develop and validate a curriculum-based measurement for oral reading fluency (CBM-ORF) tailored to assess Arabic language students' reading abilities and create preliminary norms for students from second to sixth grades. Methods and Procedures: Various forms of the CBM-ORF were developed and administered to a sample of 414 students. After data analysis, the students' readings were rated by teachers to compare the CBM-ORF with an independent measure. Outcomes and Results: The results indicate that the CBM-ORF exhibits strong reliability and validity, making it a valuable tool for monitoring progress and identifying reading difficulties in Arabic readers. Furthermore, ORF norms have been established and proposed. Conclusions and Implications: This study emphasizes the absence of a valid reading tool for Arabic language students. It offers resources for teachers to make data-driven decisions, especially for students with learning disabilities.